RISK MITIGATION STRATEGY OF TURN AROUND MATERIAL SUPPLY CHAIN WITH HOUSE OF RISK (HOR) METHOD AT PT PUPUK ISKANDAR MUDA - Putra, Hendrawan Syah; Arhami, Arhami; Irwansyah, Irwansyah (International Journal of Multidisciplinary Research and Literature, 2025)
For maintaining the reliability of the production process at PT Pupuk Iskandar Muda, routine maintenance of production equipment is needed, such as the implementation of Turn Around. The implementation of Turn Around is carried out every 18 to 24 months. In Turn Around planning, critical materials must be available during the Turn Around. So that the Turn Around material procurement process must be effective and efficient. The complexity of supply chain activities of Turn Around material procurement process involving many parties and the uncertainty that occurs in very rapid dynamic changes does not rule out the possibility of risk events that have negative impacts in the short term and long term. For this reason, it is necessary to conduct research that aims to obtain risk events, risk agents and mitigation action formulations. The method used in the study is the House of Risk (HOR) to obtain risk events, risk agents and design mitigation action formulations for priority risk agents based on the Aggregate Risk Potential (ARP) value that can suppress the emergence of risk agents. The results of the study obtained 32 risk events and 21 risk agents. Priority risk agents based on the highest ARP value of 10 risk agents that have an impact of 80.78% of the occurrence of risk events. There are 9 risk mitigation actions that can suppress the emergence of risk agents in the supply chain of the Turn Around material procurement process.